2012
DOI: 10.1242/jcs.101550
|View full text |Cite
|
Sign up to set email alerts
|

Increased retinoic acid levels through ablation of Cyp26b1 determine the processes of embryonic skin barrier formation and peridermal development

Abstract: SummaryThe process by which the periderm transitions to stratified epidermis with the establishment of the skin barrier is unknown. Understanding the cellular and molecular processes involved is crucial for the treatment of human pathologies, where abnormal skin development and barrier dysfunction are associated with hypothermia and perinatal dehydration. For the first time, we demonstrate that retinoic acid (RA) levels are important for periderm desquamation, embryonic skin differentiation and barrier formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 56 publications
3
41
0
Order By: Relevance
“…Lucifer yellow (LY) dye with 0.95 nm in diameter cannot penetrate into the epidermis [21], therefore it was utilized to examine the epidermal barrier functions against external assaults. In particular, the outside-in barrier function in the stratum corneum would be an important target to evaluate [15, 22]; therefore, the recently developed in vivo dye penetration assay [14] was used in this study. Consistent with previous studies [15, 22], we found that positive signals were confined to hair follicles and to the outer surface of the stratum corneum in the control mice (Fig 2A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lucifer yellow (LY) dye with 0.95 nm in diameter cannot penetrate into the epidermis [21], therefore it was utilized to examine the epidermal barrier functions against external assaults. In particular, the outside-in barrier function in the stratum corneum would be an important target to evaluate [15, 22]; therefore, the recently developed in vivo dye penetration assay [14] was used in this study. Consistent with previous studies [15, 22], we found that positive signals were confined to hair follicles and to the outer surface of the stratum corneum in the control mice (Fig 2A).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the outside-in barrier function in the stratum corneum would be an important target to evaluate [15, 22]; therefore, the recently developed in vivo dye penetration assay [14] was used in this study. Consistent with previous studies [15, 22], we found that positive signals were confined to hair follicles and to the outer surface of the stratum corneum in the control mice (Fig 2A). By contrast, LY signals were sporadically observed in the stratum corneum of the diabetic mice (Fig 2A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ATRA induces a catagen-like stage in human hair follicles, presumably via up-regulation of TGF-β2 in the dermal papilla, resulting in hair loss [62]. In a mouse model which knocked out cytochrome P450, family 26, subfamily b, polypeptide 1 (Cyp26b1), which encodes an RA-degrading enzyme, the in vivo administration of RA to pregnant mice or its addition to skin cultures demonstrated that appropriate RA levels are important for periderm desquamation, embryonic skin differentiation, and barrier formation in the developing mammalian skin [26]. Furthermore knock-out mouse lacking Cyp26b1 in their skin exhibit major hair follicle development defects [27].…”
Section: Development Of Skin In Retinoid Signaling Deficient Micementioning
confidence: 99%
“…Interestingly, ATRA-induced expression of Tgm2 (transglutaminase 2) and Gbx1 in the epidermis and that of TGF-β2 expression in the dermis are required for the mucosal transdifferentiation [22]. Other than the transdifferentiation, RA also plays an important role in barrier formation and hair follicle formation in skin [6,7,[23][24][25][26][27]. This review highlights our current understanding of the role of retinoic acid in the epidermal transdifferentiation of skin and its appendages.…”
Section: Introductionmentioning
confidence: 99%